Effect of increased load of high-strength food wastewater in thermophilic and mesophilic anaerobic co-digestion of waste activated sludge on bacterial community structure. (1st August 2016) - Jang, Hyun Min; Ha, Jeong Hyub; Kim, Mi-Sun; Kim, Jong-Oh; Kim, Young Mo; Park, Jong Moon
Abstract: In recent years, anaerobic co-digestion (AcoD) has been widely used to improve reactor performance, especially methane production. In this study, we applied two different operating temperatures (thermophilic and mesophilic) and gradually increased the load of food wastewater (FWW) to investigate the bacterial communities during the AcoD of waste activated sludge (WAS) and FWW. As the load of FWW was increased, methane production rate (MPR; L CH4 /L d) and methane content (%) in both Thermophilic AcoD (TAcoD) and Mesophilic AcoD (MAcoD) increased significantly; the highest MPR and methane content in TAcoD (1.423 L CH4 /L d and 68.24%) and MAcoD (1.233 L CH4 /L d and 65.21%) were observed when the FWW mixing ratio was 75%. However, MPR and methane yield in both reactors decreased markedly and methane production in TAcoD ceased completely when only FWW was fed into the reactor, resulting from acidification of the reactor caused by accumulation of organic acids. Pyrosequencing analysis revealed a decrease in bacterial diversity in TAcoD and a markedly different composition of bacterial communities between TAcoD and MAcoD with an increase in FWW load. For example, Bacterial members belonging to two genera Petrotoga (assigned to phylum Thermotogae ) and Petrimonas (assigned to phylum Bacteroidetes ) became dominant in TAcoD and MAcoD with an increase in FWW load, respectively. In addition, quantitative real-time PCR (qPCR) results showed higher bacterial and archaeal populations (expressed as 16S rRNA gene concentration) in TAcoD than MAcoD with an increase in FWW load and showed maximum population when the FWW mixing ratio was 75% in both reactors. Collectively, this study demonstrated the dynamics of key bacterial communities in TAcoD and MAcoD, which were highly affected by the load of FWW. Graphical abstract: Highlights: Thermophilic and mesophilic anaerobic co-digestion of WAS and FWW was examined. Peak MPR in both reactors was observed when FWW mixing ratio was 75%. Bacterial diversity in TAcoD gradually decreased with increase in FWW load. Genus Petrotoga became dominant in TAcoD with increase in FWW load. Genus Petrimonas became dominant in MAcoD with increase in FWW load.